Documenting Scottish Architectural Cast Iron in Argentina - Lucia Juarez (ABE Journal)
This article will consider the process of documenting cast iron pieces and products located in Argentina, but manufactured by three of Scotland’s most important foundries: Carron Company, Saracen (Macfarlane) and Lion. It draws on work done mainly in Scottish archives, and is part of a more extensive project being undertaken at the University of Edinburgh in conjunction with Historic Scotland, entitled “Trading Nations: Architecture, Informal Empire, and the Scottish Cast Iron Industry in Argentina.”Argentina underwent its most intense period of population growth between 1880 and 1930. Owing mainly to European immigration, this drastic demographic change was accompanied by the most intensive urbanization process in the country’s history. Many of the buildings erected between the 1850s and 1930s used iron, especially prefabricated cast iron, for whole buildings, structural parts, or ornamentation. The cast iron elements, sold via trade catalogues, had been widely used in Europe, but were virtually unknown in Argentina. Cast iron became crucial to the process of modernization.At the time, Scotland enjoyed a commanding position in the pre-fabricated ironwork industry. In Latin America, Argentina’s rapid industrialization, increased wealth, and strategic importance to British national interests made the country a significant market for Scottish ironwork.Some of these cast iron elements manufactured in Scotland and shipped to Argentina still survive, and are part of a transnational architecture that today represents a shared heritage yet to be fully revealed. This paper identifies some of the products made at the Carron, Saracen, and Lion foundries, among the most important iron foundries in architectural cast iron development in Scotland.